2020
DOI: 10.1038/s41467-020-15124-z
|View full text |Cite|
|
Sign up to set email alerts
|

Crystal structure of a lipin/Pah phosphatidic acid phosphatase

Abstract: Lipin/Pah phosphatidic acid phosphatases (PAPs) generate diacylglycerol to regulate triglyceride synthesis and cellular signaling. Inactivating mutations cause rhabdomyolysis, autoinflammatory disease, and aberrant fat storage. Disease-mutations cluster within the conserved N-Lip and CLip regions that are separated by 500-residues in humans. To understand how the N-Lip and CLip combine for PAP function, we determined crystal structures of Tetrahymena thermophila Pah2 (Tt Pah2) that directly fuses the N-Lip and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 57 publications
4
37
0
Order By: Relevance
“…A canonical haloacid dehalogenase catalytic site is contained in the C-terminal domain and N-terminal amphipathic helices and a polybasic domain facilitate membrane interaction [ 4 , 9 ] ( Figure 2 A). Recent crystallization studies have suggested that these conserved termini interact to form an immunoglobulin-like domain that is enabled by the variable regions in the middle of the protein [ 12 ] ( Figure 2 B). There is also evidence that lipin proteins form hetero- and homo-oligomers in their native state [ 13 ], although the importance of oligomer formation is still unclear.…”
Section: Lipin Protein Structure and Regulationmentioning
confidence: 99%
“…A canonical haloacid dehalogenase catalytic site is contained in the C-terminal domain and N-terminal amphipathic helices and a polybasic domain facilitate membrane interaction [ 4 , 9 ] ( Figure 2 A). Recent crystallization studies have suggested that these conserved termini interact to form an immunoglobulin-like domain that is enabled by the variable regions in the middle of the protein [ 12 ] ( Figure 2 B). There is also evidence that lipin proteins form hetero- and homo-oligomers in their native state [ 13 ], although the importance of oligomer formation is still unclear.…”
Section: Lipin Protein Structure and Regulationmentioning
confidence: 99%
“…This includes the cell cycle (Bahmanyar et al, 2014), mechanical stress (Romani et al, 2019), nutrition (Peterson et al, 2011), anoxia (MacVicar et al, 2019, membrane composition (Eaton et al, 2013;Karanasios et al, 2010), and when cells alter morphology (Yang et al, 2020). Lipin is a large > 100kD soluble enzyme (Khayyo et al, 2020) that receives extensive post-translational modifications: acetylation, sumoylation, ubiquitination, and phosphorylation have all been described (Harris et al, 2007;Li et al, 2018;Liu and Gerace, 2009;O'Hara et al, 2006;Shimizu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lipin PA phosphatase activity requires that the N-terminus inserts into the membrane as an amphipathic helix (Khayyo et al, 2020). This event is inhibited by phosphorylation, which reduces Lipin PA phosphatase activity (Eaton et al, 2013;Huffman et al, 2002;Karanasios et al, 2010;O'Hara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas yeast PAP is also known as Pah1, the mouse and human forms of PAP, which are encoded by the Lpin 1, 2, and 3 and LPIN 1, 2, and 3 genes, respectively, are also known as lipin (10,11). In organisms studied thus far, PAP activity is dependent on the DXDX(T/V) catalytic motif in the haloacid dehalogenase (HAD)-like domain (10,13,14). The enzyme is extensively modified posttranslationally by phosphorylation, which acutely regulates its catalytic activity, subcellular localization, and protein stability (15)(16)(17).…”
Section: Pap Is An Important Enzyme In Lipid Metabolismmentioning
confidence: 99%
“…In the radioactive PAP assay, the substrate PA contains a radiolabel in the phosphate moiety (e.g., 32 P) or in the glycerol backbone or the fatty acyl moieties (e.g., 14 synthesized from DAG and [ -32 P]ATP by DAG kinase (Fig. 2, reaction 1 (88,89)).…”
Section: Radioactive Assaysmentioning
confidence: 99%